2017
DOI: 10.1101/142588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chondroitin Sulfate Elicits Systemic Pathogenesis In Mice By Interfering With Gut Microbiota Homeostasis

Abstract: Whether chondroitin sulfate (CS), a common ingredient naturally occurring in livestock and poultry products, improves osteoarthritis remains debating.Here, we show for the first time that CS induces steatogenesis, atherogenesis, and dementia-like pathogenesis in mice. Gut microbiome analysis revealed the sulfatase-secreting bacteria Rikenella and the sulfate-reducing bacteria Desulfovibrio are enriched. Surprisingly, berberine use boosts CS-induced multi-loci inflammatory manifestations by further increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…However, it remains inclusive why CS.NM with the overgrown SSB (A.muciniphila) does not show synovitis. In our recent finding, A.muciniphila was observed to induce mucin expression and reinforce mucus integrity, thereby compromising LPS-mediated pro-inflammatory stimuli [33]. Accumulating evidence supports that A. muciniphila has therapeutic values in metabolic diseases, including an inverse correlation of A. muciniphila with obesity and diabetes in mice and humans [34,35].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it remains inclusive why CS.NM with the overgrown SSB (A.muciniphila) does not show synovitis. In our recent finding, A.muciniphila was observed to induce mucin expression and reinforce mucus integrity, thereby compromising LPS-mediated pro-inflammatory stimuli [33]. Accumulating evidence supports that A. muciniphila has therapeutic values in metabolic diseases, including an inverse correlation of A. muciniphila with obesity and diabetes in mice and humans [34,35].…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, we found in the present study that LPS upregulates the NALFD-related genes in a large scale. However, our recent work indicated that most of the NALFD-related genes are downregulated in CS mice as compared with AL mice [33]. The latter result addressed that CS might not raise the hepatic LPS level to upregulate the NALFD-related genes, otherwise it should have reduced the hepatic LPS level to downregulate the NALFD-related genes.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, cephalosporin significantly mitigated colonic mucus lesions and delayed the early pathogenesis of dementia, steatohepatitis, and atherosclerosis. Berberine significantly aggravated colonic mucus lesions and enhanced multi-systemic pathogenesis (Liao et al, 2017a ). It has also been observed that germ-free rats had thinner colonic mucus layers, suggesting that microbial colonization is required for mucin production (Desai et al, 2016 ).…”
Section: Proinflammatory Activity Of Cs-promoted Ssb and Anti- Inflammentioning
confidence: 99%
“…Administration of Lactobacillus johnsonii N6.2 considerably decreases the happening of indigestion, abdominal pain, and cephalic syndromes were observed. Additionally, some studies demonstrated that monocytes and natural killer cell numbers were increased significantly and an increase of circulating effector Th1 cells (CD45RO +CD183+CD196−) and cytotoxic CD8+T cells subset was observed in the Lactobacillus johnsonii N6.2 group [109,112].…”
Section: Management Of Diabetes and Obesitymentioning
confidence: 99%
“…Current review study revealed that construction of a recombinant strain of Lactobacillus gasseri, Lactobacillus paracasei elicits various health benefits through its antimicrobial activity, bacteriocin production, and immunomodulation of the innate and adaptive systems therefore had significantly reduced blood glucose levels and increased insulin levels [109][110][111]. Also Lactobacillus species such as: Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus paracasei, Lactobacillus bulgaricus have been known to improve obesity-associated metabolic problems.…”
Section: Management Of Diabetes and Obesitymentioning
confidence: 99%